(untitled) (Fiep Bulletin - online, 2011)
The boarding of the study is the adaptation of the current education for an education of partnership with emphasis in the changes in the educational context of form to stimulate the children and young to also give importance to the informal experiences of day-by-day. The partnership process is considered as the primary object of the education, that it shows not only intellectually, but also experimentally that partnership relations are possible, it is draw attention to the cognitive or intellectual learning and also in affective and the emotional one. The study it has as objective main to present the psychological factors directed toward a partnership model that in such a way praises the capacity of innovation for an autonomy in the relation of the educational management as well as of the proper perception of each being - human. One is about an inspired bibliographical research in the workmanship of Riane Eisler - Tomorrow’ s Children: The Blueprint will be Partnership Education will be the 21st Century (2000) that study the relations between the responsible human beings for the transformations of life. Identifications of psychologists are told who point that the type of care (material, emotional and mental) that the child receives mainly during first the three years of life opens neural ways that will determine great part of our when adult mental capacity and emotional structure. The process of education of partnership is an education style, that integrates and honors the students as complete individuals in the diverse styles of learning.